2006
DOI: 10.1037/0278-7393.32.2.425
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic prediction in language comprehension: Evidence from either...or.

Abstract: Readers' eye movements were monitored as they read sentences in which two noun phrases or two independent clauses were connected by the word or (NP-coordination and S-coordination, respectively). The word either could be present or absent earlier in the sentence. When either was present, the material immediately following or was read more quickly, across both sentence types. In addition, there was evidence that readers misanalyzed the S-coordination structure as an NPcoordination structure only when either was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
169
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(183 citation statements)
references
References 54 publications
6
169
0
1
Order By: Relevance
“…This account would emphasize the indirect nature of the evidence in favor of the claim that the ultimately correct analysis was, in fact, adopted prior to the main point of ambiguity in the critical conditions. This evidence comes from previous studies (Staub & Clifton, 2006;Frazier et al, 2000) that were not explicitly designed to investigate the parser's analysis at the relevant points (i.e., at the point of reading or in Experiment 1, and at the point of reading the subordinate clause verb in Experiment 2), and from sentence completion studies carried out in association with the present eyetracking experiments which found, first, that when sentence-initial either was present, or is about twoand-a-half times as likely to be treated as a clausal coordinator as when either was absent, and second, that a completion with a subordinate clause-final verb phrase was significantly more likely to consist of a simple intransitive verb when this verb phrase was preceded by verb and.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…This account would emphasize the indirect nature of the evidence in favor of the claim that the ultimately correct analysis was, in fact, adopted prior to the main point of ambiguity in the critical conditions. This evidence comes from previous studies (Staub & Clifton, 2006;Frazier et al, 2000) that were not explicitly designed to investigate the parser's analysis at the relevant points (i.e., at the point of reading or in Experiment 1, and at the point of reading the subordinate clause verb in Experiment 2), and from sentence completion studies carried out in association with the present eyetracking experiments which found, first, that when sentence-initial either was present, or is about twoand-a-half times as likely to be treated as a clausal coordinator as when either was absent, and second, that a completion with a subordinate clause-final verb phrase was significantly more likely to consist of a simple intransitive verb when this verb phrase was preceded by verb and.…”
Section: Discussionmentioning
confidence: 54%
“…This finding could be interpreted as reflecting the mild reanalysis that is predicted to take place on the ambiguous noun phrase in the either no comma condition. As noted above, Staub and Clifton (2006) found that in general an or noun phrase string is read more quickly when either is present than when either is absent. In the present experiment, then, it is possible that the one-versus-three pattern resulted from a combination of this facilitation from either and a reanalysis effect, working in the opposite direction, in the either no comma condition.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations